Pengaruh Naungan dan Panjang Stek terhadap Iklim Mikro dan Pertumbuhan Tanaman Bayam Brazil (Alternanthera sissoo) - Sumiahadi, Ade; Wisesa, Abi Mayu (Universitas Gadjah Mada, 2025)
Brazilian spinach originated from the American continent and has not been widely cultivated in Indonesia. Its narrow land urban farming development is constrained by low light-intensity conditions that prevent Brazilian spinach from growing optimally. The research aimed to study the effects of shade and cutting length on the growth of Brazilian spinach plants. The research was conducted from December 2023 to January 2024 at the experimental field of the Faculty of Agriculture UMJ. The research used a split-plot design with a randomized complete block design (RCBD) as the environmental design. The treatment used as the main plot was shade consisting of no shade, 45% paranet shade, and 65% paranet shade, while the length of cuttings became a subplot consisting of 5 cm, 7 cm, and 12 cm. The treatment combinations formed are nine, and were repeated 3 times. The results showed that shading increased humidity and decreased temperature and light intensity in the plant microenvironment. At the end of the study, in general, the provision of paranet shade up to 65% did not significantly affect Brazilian spinach plants' growth except for plant height and root length. The cutting length had no significant effect on all observed variables. The use of 5 cm cutting length is recommended because it is considered more efficient in providing cutting material. There were no interaction effects between shade and cutting length on the growth of Brazilian spinach plants.